Fitness for working in a policeman being treated for OSAS - Sanna, Antonio; Garbarino, Sergio (La Medicina del Lavoro, 2019)
A policeman who has been ill with OSAS for 10 years is in optimal CPAP therapy. During this time, the overall assessment of his work activities was excellent and he had no traffic accidents or accidents at work. Concerning his work as a policeman, the Medical Commission of 1st instance considered him unfit to work. Conversely, the Medical Commission of 2nd instance declared him fit to work. In the adult general population, the prevalence of moderate and severe OSAS is more than 20%. It is therefore likely that there are many policemen affected by OSAS and the number of requests for assessments of fitness to work in those with OSAS will increase. It is a priority: (i) to integrate the training course of the medical staff of the Police Forces and the Armed Forces with updates on OSAS; (ii) to delete OSAS from the list of chronic diseases for which night shift work is not indicated.